Representing Rumah Tahfidz in strengthening of socio-political agenda in contemporary Indonesia: Motive, contestation, and perception - Mizwar Hasyim, Nanang; Izudin, Ahmad; Yafik Mursyid, Achmad (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - This study explores the important role of music in practical implications for the modern Islamic da'wah context. Method - This study uses library research, with integrative and connective literature analysis as the main method, to connect various perspectives from various previous studies. Result - Music in Islamic da'wah is not just a means of conveying messages but a transformative force capable of stirring emotions, building deep spiritual bonds, and challenging the traditional boundaries of da'wah. With its ability to trigger emotional feelings, compassion, and spiritual reflection, music can make religious messages more alive and relevant amidst the dynamics of the modern world. Implication – The use of music in conveying Islamic messages through da'wah must consider ethics, content regulations, and understanding of different cultures. In facing this challenge, intercultural collaboration, education, and awareness of the impact of music in a religious context are needed. Originality/Value - Music is not just a medium but a tool capable of helping individuals internalize religious values, facilitating more profound understanding, and stimulating deep spiritual reflection in humans.*** Tujuan - Penelitian ini mengeksplorasi peran penting musik dalam implikasi praktis untuk konteks dakwah Islam modern. Metode - Penelitian ini menggunakan penelitian kepustakaan, dengan analisis literatur integratif dan konektif sebagai metode utama, untuk menghubungkan berbagai perspektif dari berbagai penelitian sebelumnya. Hasil - Musik dalam dakwah Islam bukan hanya sekedar alat penyampai pesan, melainkan sebuah kekuatan transformatif yang mampu menggugah emosi, membangun ikatan spiritual yang mendalam, dan menantang batas-batas tradisional dakwah. Dengan kemampuannya untuk memicu perasaan emosional, kasih sayang, dan refleksi spiritual, musik dapat membuat pesan-pesan agama menjadi lebih hidup dan relevan di tengah dinamika dunia modern. Implikasi - Penggunaan musik dalam menyampaikan pesan-pesan Islam melalui dakwah harus memperhatikan etika, regulasi konten, dan pemahaman terhadap budaya yang berbeda. Dalam menghadapi tantangan ini, kolaborasi antar budaya, pendidikan, dan kesadaran akan dampak musik dalam konteks agama sangat dibutuhkan. Orisinalitas/ Nilai - Musik bukan hanya sekedar media, melainkan alat yang mampu membantu individu untuk menginternalisasi nilai-nilai agama, memfasilitasi pemahaman yang lebih mendalam, dan menstimulasi refleksi spiritual yang dalam pada diri manusia.